Niacin supplementation increases the number of oxidative type I fibers in skeletal muscle of growing pigs - Khan, Muckta; Mooren, Frank-Christoph; Ringseis, Robert; Krüger, Karsten; Most, Erika; Eder, Klaus; Justus Liebig University Giessen (My University, 2013)
Background: A recent study showed that niacin supplementation counteracts the obesity-induced muscle fiber switching from oxidative type I to glycolytic type II and increases the number of type I fibers in skeletal muscle of obese Zucker rats. These effects were likely mediated by the induction of key regulators of fiber transition, PGC-alpha and PGC-beta, leading to muscle fiber switching and up-regulation of genes involved in mitochondrial fatty acid import and oxidation, citrate cycle, oxidative phosphorylation, mitochondrial biogenesis. The aim of the present study was to investigate whether niacin supplementation causes type II to type I muscle and changes the metabolic phenotype of skeletal muscles in growing pigs.Results: 25 male, 11 wk old crossbred pigs (Danzucht x Pietrain) with an average body weight of 32.8 ± 1.3 (mean ± SD) kg were randomly allocated to two groups of 12 (control group) and 13 pigs (niacin group) which were fed either a control diet or a diet supplemented with 750 mg niacin/kg diet. After 3 wk, the percentage number of type I fibers in three different muscles (M. longissismus dorsi, M. quadriceps femoris, M. gastrocnemius) was greater in the niacin group and the percentage number of type II fibers was lower in the niacin group than in the control group (P < 0.05). The mRNA levels of PGC-beta and genes involved in mitochondrial fatty acid catabolism (CACT, FATP1, OCTN2), citrate cycle (SDHA), oxidative phosphorylation (COX4/1, COX6A1), and thermogenesis (UCP3) in M. longissimus dorsi were greater in the niacin group than in the control group (P < 0.05).Conclusions: The study demonstrates that niacin supplementation induces type II to type I muscle fiber switching, and thereby an oxidative metabolic phenotype of skeletal muscle in pigs. Given that oxidative muscle types tend to develop dark, firm and dry pork in response to intense physical activity and/or high psychological stress levels preslaughter, a niacin-induced change in the muscle´s fiber type distribution may influence meat quality of pigs.
Keywords: Niacin; pig; muscle fiber transition; oxidative type I fiber; ddc:610